Cavity-rate analysis applied to the frequency oscillations relaxation in a self-pulsed large-mode-area ytterbium-doped fiber laser. - Toral Acosta, Daniel; Selvas Aguilar, Romeo; García Ramírez, Mario Alberto (Universidad Autónoma de Nuevo León, 2015)
In this work, an analysis for a self-pulsing behavior within a large-mode-area Ytterbium-doped fibre laser operated as a free running laser is presented. A set of equations that describes the relaxation oscillations frequency by considering a cavity as well as the atomic rate equations were obtained. In here, the behaviour of the self-pulsing is due to the un-pumped fibre section that plays a key role for the saturate absorber. Analytical results depicts that instead of reaching a continuous wave-based regime, the laser output will show pulses with an increasing repetition rate due to the pump power is higher. It is in good agreement with the natural behaviour observed within this fibre laser.